Tree-ring δ18O and δ2H stable isotopes reflect the global meteoric water line - Arosio, Tito; Büntgen, Ulf; Nicolussi, Kurt; Moseley, Gina E.; Saurer, Matthias; Pichler, Thomas; Smith, M. Paul; Gutierrez, Emilia; Andreu-Hayles, Laia; Hajdas, Irka; Bebchuk, Tatiana; Leuenberger, Markus (Frontiers in Earth Science, 2024)
IntroductionThe Global Meteoric Water Line (GMWL) describes the linear relationship between stable hydrogen (δ2H) and oxygen (δ18O) isotopes in precipitation over large spatial scales and therefore represents a unique reference for water isotopic values. Although trees have the potential to capture the isotopic composition of precipitation, it remains unclear if the GMWL can be reconstructed from tree-ring stable isotopes, since δ18O and δ2H undergo in vivo physiological fractionation.MethodsWe analyze the tree rings δ18O and δ2H values from six regions along a latitudinal gradient from Spain to Greenland. ResultsThe data show that the covariance between δ18O and δ2H closely follows the GMWL, which reflects the isotopic signature of large-scale precipitation patterns. We show that changes in regional tree-ring δ18O and δ2H values along wide latitudinal ranges are influenced by the isotopic composition of precipitation with temperature and latitude being the most significant drivers of spatial variation across the studied regions. In contrast, local tree-ring δ18O and δ2H values are mainly controlled by plant physiological fractionation processes that mask the isotopic signature of precipitation.ConclusionWe conclude that covariance in tree-ring δ18O and δ2H reflects the GMWL at larger spatial scales, but not when evaluating them at individual sites.